Studi performa aerodinamis turbin hidrokinetik Savonius dengan 2 semicircular blade-sharp leading edge - Khoiri Rozi; Berkah Fajar; M. Rasyid (METAL: Jurnal Sistem Mekanik dan Termal, 2022)
This current investigation was conducted to study the aerodynamic characteristics of Savonius hydrokinetics turbine with semicircular blade-sharp leading edge. The influences of blade thickness and freestream velocity were simulated using ANSYS FLUENT with k-w SST model. The results show that the flow structure changes with increasing turbine rotation in which the flow complexity is formed at a larger rotation angle. The coefficient of torque and power for thin blades is higher than for thicker turbine blades and its values increase with the increase in the freestream velocity.